Prostorski stroji gledališča kot dinamika prestopanja meja semiotičnih sistemov - Toporišič, Tomaž (Ars et humanitas, 2019)
On the basis of a study of six examples from contemporary theatre and performing arts, the essay will examine how Lotman's concept of the semiosphere as an ecosystem covering both the space and time of performance can be applied to the environmental, economic and political aspects of the theatrical within the post-colonial and intercultural space. His notion of the semiosphere as a spatio-temporal phenomenon, a combination of different (non)verbal languages that are in constant dialogue with one another, will be used for the analysis of spatial relations and space policies within contemporary performing arts in order to discover how the act of mise en scene creates semiotic languages, which are not a simple sum of individual systems, but are characterised as a dynamic interactivity, establishing the theatrical event. The subject of the analysis will be theatrical performances as semiotic spaces of transitional forms that arise between different media, the crossing of the boundaries between the stage and the auditorium, changes in the dynamics of relations between actors and spectators within the process of creation and reception. We will link Lotman's "theatre's position as an intermediary between the moving and nondiscrete real world and the immobile and discrete world of the representational arts" (Lotman, Universe of the Mind) to Jacques Ranciere's notion of an emancipated spectator and Nicolas Bourriaud's notion of translation, art as an exploration of the bonds that engulf the word and picture, time, and space. Our aim will be to research the dynamics of semiotic languages within space, the interactivity they establish within performative practice.
Keywords: dramaturgija zvoka; dramaturgy of sound; Emmanuel Demarcy-Mota; prostorska dramaturgija; prostorski obrat; Robert Wilson; semiosfera; semiosphere; spatial dramaturgy; spatial turn; Vito Taufer